1994
DOI: 10.1677/jme.0.0130275
|View full text |Cite
|
Sign up to set email alerts
|

In vitro binding of 3,5-di-iodo-L-thyronine to rat liver mitochondria

Abstract: In this study we have demonstrated that specific binding sites for 3,5-di-iodo-L-thyronine (3,5-T2) can be detected in rat liver mitochondria. After incubation with the homogenate, liver mitochondria bound only a small portion of [3,5-125I]T2. The addition of a 100-fold excess of unlabelled 3,5-T2 caused the displacement of on average 50-60% of the [3,5-125I]T2 bound. Specific binding of 3,5-T2 to rat liver mitochondria occurred rapidly; a maximum was achieved after 5 min. Maximal binding was obtained at 37 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…Possibly, the effect of 3,5-T2 may be consequent upon a direct interaction of 3,5-T2 with mitochondria. Our previous studies showing the presence of specific binding sites for 3,5-T2 in rat liver mitochondria [9] and direct interaction of 3,5-T2 with isolated CO complexes [10] are consistent with this notion. In addition, O' Reilly and Murphy [23] have reported that the stimulatory effect exerted by 3,5-T2 on rat liver mitochondrial respiration is independent of the protein synthesis.…”
Section: Role Of 35-t2supporting
confidence: 85%
“…Possibly, the effect of 3,5-T2 may be consequent upon a direct interaction of 3,5-T2 with mitochondria. Our previous studies showing the presence of specific binding sites for 3,5-T2 in rat liver mitochondria [9] and direct interaction of 3,5-T2 with isolated CO complexes [10] are consistent with this notion. In addition, O' Reilly and Murphy [23] have reported that the stimulatory effect exerted by 3,5-T2 on rat liver mitochondrial respiration is independent of the protein synthesis.…”
Section: Role Of 35-t2supporting
confidence: 85%
“…We speculated that the mitochondrial respiratory complexes II and IV could be direct targets for the short-term actions of GH, by analogy to what has been previously demonstrated for 3′,5′di-iodothyronine (T2). Although the direct mitochondrial effect obtained with T2 may result from a different molecular mechanism owing to its chemical structure, it has been reported in addition to the detection of T2-binding sites in the organelle [3,37,38] that T2 can bind to a subunit of COX, leading to a conformational change of the enzyme. Moreover, D’Alecy et al [39] have shown that a peptide hormone, the glucagon, that stimulated respiration via its membrane receptor by activation of adenylate cyclase, could directly act on isolated mitochondria and specifically alter oxidative metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Recent pharmacological applications of 3,5-T2 mainly in hypothyroid rodent models (3,4) challenged this hypothesis because they revealed rapid and chronic metabolic changes, partly independent of the classical T3 receptors (TR). 3,5-T2 rapidly enhanced hepatic oxygen consumption (5,6), and hepatic mitochondria were identified as specific targets (7,8). Moreover, 3,5-T2 was suggested to influence glucose metabolism by stimulating glucose-6-phosphate dehydrogenase (G6PD) activity (9) or by modulating gluconeogenesis via sirtuin 1 (10,11).…”
mentioning
confidence: 99%